Algorithm development and case study for the site evaluation process of small scale wind turbines according to the ABNT NBR IEC 61400-12-1 - JoÃo Victor Pinto da Silveira (2015)
The main objective of this work is to present a site evaluation study for the Power performance generator of small scale wind turbines (AEPP). The Brazilian norm ABNT NBR IEC 61400-12-1 and its annexes A (obstacle valuation) and B (terrain assessment) were used as reference. Two source codes were written in the R language in order to automate the evaluation process. Both source codes were validated through direct comparison between the results of the developed R codes and the results obtained by DNV GL, which has ISO17025 international laboratory certification for power performance measurements of wind turbines according to the IEC standard. The validated code was then used to evaluate possible positions for the AEPP power performance measurement in UFC. The topographic map was downloaded from the free database SRTM and the characteristic obstacles were determined by satellite images and photos of the area. Altogether, three areas and their respective pairs AEPP â anemometric tower were analyzed regarding their available measurement sector and the necessity or not to perform site calibration.